(untitled) (BIRDEM Medical Journal, 2024)
Sturge-Weber syndrome is a rare congenital, non-familial sporadic condition also known as encephalotrigeminal angiomatosis, is a phakomatoses consisting of neurological, skin and ocular manifestations. Symptoms reported varies in severity and age of onset but it is commonly detected in infancy. The Ophthalmic feature of this disease consists of glaucoma and is also associated with vascular manifestation of the conjunctiva, epi-sclera, choroid and retina. In the present case, a 19-year-old male presented with a port wine stain on the right side of the face, leptomeningeal angioma, ocular hypertension, temporal hemianopia of the left eye and choroidal hemangioma with macular scar of the right eye, seizure and weakness of the left side of the body. The purpose of presenting the case is to illustrate both the characteristic presentation and to underline the importance of its diagnosis in the clinical ophthalmological practice. BIRDEM Med J 2024; 14(3): 166-169